Uneven Distribution of Novice Teachers in the Chilean Primary School System - Meckes, Lorena; Bascopé, Martín (Education Policy Analysis Archives, 2012)
This study examines the allocation of novice primary teachers in Chilean schools, looking at their characteristics and at the attributes of the schools at which they are hired after having completed their initial teacher training. The study reveals that in Chile, more qualified novice teachers are more prone to get jobs in socio-economically advantaged schools or in schools with better academic outcomes. In contrast, in disadvantaged schools, it is more likely to find novice teachers with poor results on their exit exams and who come from socioeconomic backgrounds similar to those of the school populations. These findings provide new data to inform Chilean policies. Thus, achieving a more equitable distribution of highly qualified teachers is a challenge for Chile if the aim is to reduce the achievement gap between schools attended by pupils of higher and lower socioeconomic status. Furthermore, these findings might shed some light on the current debate surrounding teacher education policies. A new law will mandate that novice teachers pass the exit exam that until now they have taken voluntarily in order to be hired in any publicly funded school. This study provides support and evidence to inform the debate that will follow in parliament, since we found that novice teachers performing at a very low level—perhaps below the minimum that will be required—have a high probability of ending up working in schools in more disadvantaged areas. On a more general scale, this research also provides a simple but complete methodology that can be used to study issues of teacher distribution elsewhere.